Safety, Efectiveness, and Immunogenicity 6 Months After BNT162B2 mRNA Vaccine in Frail Nursing Home Residents - Montejano Hervás, Pablo; Gómez Pavón, Francisco Javier; Tornero Torres, Olga; Valverde Moyar, Mª Victoria; Martín Cruz, Beatriz; Vela Carbonera, Maribel; Tejada González, Pilar; González Becerra, Margarita; Higueras Sánchez, Esther; Ramos Cordero, Primitivo (My University, 2022)
Background Elderly people who reside in long-term care facilities form a frail and vulnerable population, with multiple pathologies and high percentages of cognitive and functional disability. Objectives The aims of this study were to assess the safety of vaccination against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in frail nursing home residents and to evaluate its efectiveness 6 months after full vaccination. Design This was an ambispective observational study. Setting Residents of a long-term care facility in Madrid, Spain. Participants One hundred and thirty-seven nursing home residents (81.8% female, mean age 87.77±8.31 years) with high comorbidity (61.3% Charlson Index ¿3) and frailty (75% Clinical Frail Scale ¿7) who received the BNT162B2 mRNA vaccine. Measurements Safety data were collected to evaluate the type of adverse drug reactions and their duration, severity, and causality. Immunogenicity was tested 6 months after the primary vaccination and efectiveness was evaluated by the incidence of SARS-CoV-2 infection, the number of hospital admissions, and mortality due to coronavirus disease 2019 (COVID-19). Results Safety: Of the residents, 21.9% had some adverse reaction and 5.8% had a severe or more serious adverse reac tion. The most frequent adverse reactions were fatigue (13.1%), pyrexia (12.4%), and headache (7.3%). No association was observed between frailty (including a need for palliative care) and clinical, functional or cognitive status of the participants and the occurrence of adverse events. Immunogenicity and Efectiveness: After 6 months of vaccination, only one case of SARS-CoV-2 infection was confrmed in the vaccinated residents. Most of the nursing home residents presented positive serology (95.2%). Loss of immunogenicity was associated with older age (95.12±3.97 vs. 87.24±8.25 years; p=0.03) and no previous COVID-19 infection (16.6% vs. 70%; p<0.001). Binary logistic regression models did not reveal this association. Conclusion The BNT162B2 vaccine is well tolerated and efective in nursing home residents, independently of their clinical, functional, cognitive, or frailty characteristics. For the most part, immunogenicity has been maintained over time, regardless of comorbidity, functional status or frailty